Before the God in this Place for Good Remembrance: A Comparative Analysis of the Aramaic Votive Inscriptions from Mount Gerizim - Gudme, Anne Katrine de Hemmer (Beihefte zur Zeitschrift für die alttestamentliche Wissenschaft, 2013)
Biographical note: Anne Katrine de Hemmer Gudme, University of Copenhagen,Denmark.